The Impact of Asymmetric Information on Capital Structure Empirical Study on Indonesia Stock Exchange - admin, Aristya Dinata B12112011 (Jurnal Manajemen Update, 2016)
The importance of capital structure in both firm and economic levels has driven many researchers to examine the factors affecting the capital structure itself. Furthermore, the existence of asymmetric information can be ignored as it is a factor that surely exists in the market, especially Indonesia’s market. As the emerging market, Indonesia is very susceptible to the new information. Thus, this study is done to examine the impact of asymmetric information on capital structure on the firm listed in IDX during 2010 – 2014. The result shows that the illiquidity ratio has a positive but insignificant effect on capital structure. On the other hand, firm size showed to have negative impact on capital structure and more significant after including the control variables of GDP and Altman Z-Score Keywords: Capital Structure, Asymmetric Information, Amihud Illiquidity, Firm Size, Indonesia